2023
DOI: 10.1002/ddr.22055
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis Targeting Chimera (PROTAC) as a promising novel therapeutic modality for the treatment of triple‐negative breast cancer (TNBC)

Abstract: Breast cancer (BC) is considered one of the most prevalent malignancies impacting women worldwide, constituting 15% of all new cancer cases. It is classified according to its molecular targets into three subtypes; HR+/ERBB2‐, ERBB2+/HR+, or HR‐ and triple‐negative breast cancer (TNBC). TNBC is considered aggressive cancer with bad prognosis and poor clinical outcomes. It lacks estrogen, progesterone, and ERBB2 receptors rendering its treatment more challenging. Owing to its unresponsiveness to hormonal therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 154 publications
0
3
0
Order By: Relevance
“…Clinical trials are ongoing in patients with HR+/HER2– advanced breast cancer previously treated with endocrine therapy and CDK4/6 inhibitors. Preliminary results showed that vepdegestrant has good clinical activity and tolerance ( Li et al, 2022 ; Dogheim and Amralla, 2023 ). However, to determine the optimal use of PROTACs and their long-term safety and efficacy in breast cancer, monitoring and tracking of toxicological effects will be required in the later stages of clinical studies and drug development of PROTACs ( Qi et al, 2021 ; Li et al, 2022 ; Dogheim and Amralla, 2023 ).…”
Section: Targeted Therapymentioning
confidence: 99%
“…Clinical trials are ongoing in patients with HR+/HER2– advanced breast cancer previously treated with endocrine therapy and CDK4/6 inhibitors. Preliminary results showed that vepdegestrant has good clinical activity and tolerance ( Li et al, 2022 ; Dogheim and Amralla, 2023 ). However, to determine the optimal use of PROTACs and their long-term safety and efficacy in breast cancer, monitoring and tracking of toxicological effects will be required in the later stages of clinical studies and drug development of PROTACs ( Qi et al, 2021 ; Li et al, 2022 ; Dogheim and Amralla, 2023 ).…”
Section: Targeted Therapymentioning
confidence: 99%
“…In particular, in vitro studies have shown promise for using PROTACs as a therapeutic modality in triple-negative breast cancer (TNBC). Although the data suggests great potential, further research is needed, including in vitro and in vivo clinical trials, to fully establish the safety and efficacy of using PROTACs in TNBC treatment [ 81 ]. PROTACs have emerged as a promising class of therapeutics for lung cancer and drug resistance in recent years.…”
Section: Protacs: Targeted Management Strategy For Several Diseased C...mentioning
confidence: 99%
“…There is no evidence suggesting that any chemotherapeutic drugs have superior efficacy in the second and later lines, and new drugs or strategies are required for this population of patients. Some new therapeutic strategies for MBC such as anti-angiogenesis therapy, androgen receptor antagonists, micro-RNA based therapy, proteolysis targeting chimeric molecules (PROTACs) and others are under exploration,some of them have initially shown potential benefits ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%